Hierarchical fuzzy logic systems and controlling vehicles in computer games - Renkas, Krzysztof; Niewiadomski, Adam (Wydawnictwo Politechniki Łódzkiej, 2014)
This paper presents a possible application of fuzzy logic systems to control vehicles in computer games. A new architecture of a fuzzy logic system is here proposed: Hierarchical Fuzzy Controller, that is composed of several fuzzy controllers in their classic meaning. ”Hierarchical” means that fuzzy sets produced as output of one of fuzzy controllers are then processed as input of another fuzzy controller. The use of such a controller signiﬁcantly enhances the possibilities of computational intelligence methods in singleplayer games, i.e. where the enemy is controlled by an agent simulating real behaviour (movement, decisions, etc.). The proposal of an original architecture of Hierarchical Fuzzy Controller, built with fuzzy controllers (in the sense of Mamdani), and discussing advantages of using this architecture to control military vehicles in a 2D single-player game, in comparison to classic fuzzy controllers, are the main scope of the paper.